Brachiaria residues fertilized with nitrogen in coffee fertilization - Pedrosa, Adriene Woods; Favarin, José Laércio; Vasconcelos, Ana Luisa Soares de; Carvalho, Bruno Vasconcelos; Oliveira, Felipe Brendler; Neves, Gabriela Barbosa (Coffee Science - ISSN 1984-3909, 2014)
The use of crop residues in the cultivation of the coffee can minimize nitrogen losses and promote its efficiently use. This study aimed to evaluate how the mode of application of nitrogen in the forage, in coffee or both affects of the seedlings growth. Seedlings of Coffea arabica were planted in 25 L pots and grown in a greenhouse. Nitrogen was applied as ammonium sulfate, either directly on the coffee tree under the canopy, or sometimes on forage crop (Brachiaria brizantha cv. Marandu). This forage crop was grown in plots of 10 m2, without N, and with 150 and 300 kg ha-1 N, which this fertilization was performed approximately 45 days prior to cutting the grass. After cutting 500 g of fresh plant, the material was placed in nylon containers and placed on the vessels. Samples were harvested to determine the concentration of total-N and C/N ratio, as well as the concentration of total-N in leaf tissue of the coffee plant. In each plot after the cutting of the plants, growth rate in diameter and plant height was recorded. In a final experiment the dry matter production, leaf number and leaf area of the coffee were evaluated, as well as the rest of Brachiaria in biomass degradation. The coffee nutritional status was not impaired when the nutrient was supplied via cycling biomass of forage fertilized with nitrogen. The addition of the forage residue without nitrogen fertilization favored the immobilization of soil N and reduced the concentration of N-coffee leaf.